KNOWLEDGE, PRACTICES, AND ATTITUDE TOWARDS NEWBORN CARE BY THE MOTHERS AGED 18-49 YEARS IN THE POSTNATAL WARD AT RUKUNYU HOSPITAL IN KAMWENGE DISTRICT. A CROSS-SECTIONAL STUDY. - Tumushabe, Innocent; Kiyingi, Daisy (Student’s Journal of Health Research Africa, 2024)
Introduction Essential newborn care refers to a series of time-bound and chronologically ordered care that a baby receives at birth and early days of his or her life. Objectives of the study The main objective was to determine the knowledge, practices, and attitudes towards newborn care by mothers aged 18-49 years in the post-natal ward at Rukunyu Hospital in Kamwenge district. Methodology A cross-sectional descriptive study design was used while using a quantitative approach at the post-natal ward of Rukunyu Hospital in Kamwenge district. The researcher conveniently sampled 96 respondents from 18th June 2023 to 30th July 2023. Data was collected using self-administered questionnaires. Results Of the 96 respondents, the majority (90.6%) had heard about newborn care and all of the mothers (100%) accepted that newborn care was very important and that all babies should receive this essential care. Furthermore, 68.8% of the mothers agreed to the fact that essential newborn care practices are 100% effective in ensuring infant’s survival and well-being in their initial days of life. Finally, the respondents’ attitude towards newborn care was generally good because all mothers (100%) agreed that all newborns should be taken good care of. Conclusion The study generally revealed that at least many mothers have learned some of the common essential newborn care practices especially exclusive breastfeeding (87.5%), provision of warmth (96.9%), and bathing neonates(93.7%) but still have a challenge with performing other practices, especially cord care(84.4%) due to knowledge gap. Recommendation Government through the Ministry of Health should increase public sensitization about newborn care practices. More of the recommendations are presented in chapter five of this report.